Fibromuscular dysplasia – a case description - Leksa, Natalia; Seweryn, Bartosz; Uberman-Kluz, Dominika; Galiniak, Sabina; Kawalec, Magdalena (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Introduction. Fibromuscular dysplasia is an idiopathic, non-inflammatory and non-atherosclerotic disease that affects the walls of arteries (mostly renal and carotid arteries). Histological classification distinguishes three main types of the disease, depending on the structural changes occurring in one of the three layers of arterial vessel walls. Objective. We present here a case of fibromuscular dysplasia affecting the internal carotid arteries. Case description. This article describes the case of a 52-year-old female patient with hypertension, hyperlipidemia, and a cardiac pacemaker in whom computed tomography angiography revealed a narrowing of the internal carotid arteries without atherosclerotic symptoms. We describe the diagnostic methods and various types of treatment that the patient suffering from fibromuscular dysplasia was subjected to. Conclusions. Due to a low detection rate of fibromuscular dysplasia, if the disease is suspected, all available diagnostic methods should be employed. Taking into account the unknown etiology of the disease, it is not possible to use a preventive therapy, or a therapy focused on stalling the progression of the disease.
Keywords: fibromuscular dysplasia; arteries; computed tomography